(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Hawthorne’s Retributive Justice in The Scarlet Letter The purpose of this paper is to analyze critically Hawthorne’s concept of retributive justice in The Scarlet Letter. As a social moralizer, Hawthorne sets his action in the puritanic town of Salem where sinners are always met by that community, with a sense of superiority and arrogance. Thus, instead of showing understanding and love, the Puritans become intolerant of Hester’s sin. Though a direct descendant of a Puritan family, Hawthorne shows compassion with his heroine; however, he denies her the chance to elope with her partner, Minister Arthur Dimmesdale. Sin according to Hawthorne is a reality that must be confronted; and once a sin is committed its consequences: alienation, remorse, despair, are inescapable. To cleanse the soul, he casts heavy reliance on confession for its redemptive force.